2021
DOI: 10.1007/s40123-021-00346-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Visual Outcome After Hyperopic LASIK Using a Wavefront-Optimized Platform Versus Other Excimer Lasers in the Past Two Decades

Abstract: Introduction: Laser-assisted in-situ keratomileusis (LASIK) for the correction of hyperopia and hyperopic astigmatism is challenging and has been less studied than for the correction of myopia and myopic astigmatism. The aim of this study was to analyze the refractive outcomes of LASIK in hyperopia and hyperopic astigmatic eyes using a wave-front optimized laser platform (the Allegretto EX500 laser) and perform a historical comparison with other excimer lasers within the past two decades. Methods: A one-center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
9
1
1
Order By: Relevance
“…Their extensive analysis demonstrated an improvement in safety, efficacy, stability, and accuracy of hyperopic LASIK over this period with newer excimer lasers meeting industry standards and the EX500 exceeding industry standards. 18 In the current study, preoperative keratometry was not found to be a significant factor associated with postoperative CDVA loss. Hyperopic excimer ablation affects corneal curvature and asphericity, producing a steeper and more prolate corneal shape with induction of higher order aberrations.…”
Section: Discussioncontrasting
confidence: 52%
“…Their extensive analysis demonstrated an improvement in safety, efficacy, stability, and accuracy of hyperopic LASIK over this period with newer excimer lasers meeting industry standards and the EX500 exceeding industry standards. 18 In the current study, preoperative keratometry was not found to be a significant factor associated with postoperative CDVA loss. Hyperopic excimer ablation affects corneal curvature and asphericity, producing a steeper and more prolate corneal shape with induction of higher order aberrations.…”
Section: Discussioncontrasting
confidence: 52%
“…2 Moshirfar et al, using the Allegreto EX500 (Alcon Laboratories, Inc.) in a sample of hyperopic eyes between +3 D and +5 D, reported an UDVA of 20/20 or better in 47%, postoperative SE within 0.5 D in 60% (93% within 1 D), and loss of 1 line of CDVA in 13% (2 or more lines in 6.7%). 11 Gauthier-Fournet et al, using the Amaris 750 in a sample of high and very high hyperopia (mean sphere of +6.64 D), reported an UDVA of 20/20 or better in 60%, postoperative SE within 0.5 D in 66% (86% within 1 D), and loss of 1 line of CDVA in 10% (2 or more lines in 0%; gain of 1 or more lines in 4%). 12 Using also the Amaris 750 and a similar hyperopia range to ours (+4/6.5 D), de Ortueta et al reported refractive and visual outcomes similar to ours, with an UDVA of 20/20 or better in 40%, postoperative SE within 0.5 D in 72% (100% within 1 D), and loss of 1 or more lines of CDVA in 12% (with gain of 1 or more lines in 17%).…”
Section: Discussionmentioning
confidence: 99%
“…26 In fact, implantation of multifocal lenses in high hyperopic patients has been reported to lead up to 21.43% of patients to lose lines of corrected distance visual acuity. 27 In addition, the choice to perform a RLE procedure in younger patients should take into consideration the actual range of hyperopic correction offered by modern corneal refractive surgery, which has been shown to be up to 6-7 D. [28][29][30] In astigmatism Acceptable results have also been described for RLE in the correction of astigmatic eyes, with varying grades of residual astigmatism. [31][32][33]…”
Section: In Hyperopiamentioning
confidence: 99%